Analisis Kapitalisasi Pasar dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Danendra Zayyan Cahyarizqullah; Dhani Ichsanuddin Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify the impact of profitability, the effect of dividend policy, and analyze the moderating effect of company size on the relationship between profitability and market capitalization, as well as dividend policy and market capitalization in the banking sector in Indonesia. In this study, the researcher used banking companies that distributed their dividends consecutively during the period of 2018-2022 as the research object. This research is quantitative in nature, using secondary data as the research data with a total of 55 samples. The research was conducted using the panel data regression application, Eviews13, employing the moderation regression analysis method. The results of this study indicate that profitability has a positive and significant effect on market capitalization, and company size is able to strengthen the interaction relationship between profitability and market capitalization. However, on the other hand, dividend policy does not have a significant effect on market capitalization. The size of the company is also unable to moderate the interaction relationship between dividend policy and market capitalization.